VD_FINDINFO Jug / 2016 / 15 vom 26. Juni 2015 - VD Tribunal cantonal (2015)
IN DUBIO PRO REO, ASSASSINAT, ENTRAVE À L'ACTION PÉNALE | 112 CP, 305 CP, 42 al. 1 CP, 47 CP, 10 al. 1 CPP (CH), 10 al. 2 CPP (CH)